2019
DOI: 10.1177/1362168819872859
|View full text |Cite
|
Sign up to set email alerts
|

The effects of working memory and declarative memory on instructed second language vocabulary learning: Insights from intelligent CALL

Abstract: The extent to which learners benefit from instruction may be largely dependent on their individual abilities. However, there is relatively little work on the interaction between instructional effectiveness in second language learning and learner individual factors. In this study, we investigated the relationship between instruction, individual differences in cognitive abilities (working memory and declarative memory), and second language vocabulary acquisition in the context of web-based intelligent computer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 103 publications
(223 reference statements)
0
12
0
Order By: Relevance
“…This model assumes that processing knowledge can be effectively enhanced when textual information is simultaneously demonstrated in both verbal and pictorial forms via audio-visual input. There is ample evidence that WM plays a significant role in vocabulary learning (Ellis & Sinclair, 1996;Kim, 2018;Morra & Camba, 2009;Ruiz & Meurers, 2021;Teng & Zhang, 2021). WM, which is widely acknowledged as having limited capacity, is crucial in language learning (Baddeley, 1992).…”
Section: Working Memory (Wm) and Vocabulary Learningmentioning
confidence: 99%
“…This model assumes that processing knowledge can be effectively enhanced when textual information is simultaneously demonstrated in both verbal and pictorial forms via audio-visual input. There is ample evidence that WM plays a significant role in vocabulary learning (Ellis & Sinclair, 1996;Kim, 2018;Morra & Camba, 2009;Ruiz & Meurers, 2021;Teng & Zhang, 2021). WM, which is widely acknowledged as having limited capacity, is crucial in language learning (Baddeley, 1992).…”
Section: Working Memory (Wm) and Vocabulary Learningmentioning
confidence: 99%
“…In this study, two natural classes of the second year in a middle school in Weifang City were selected as the experimental class and the control class. e tests and surveys of the students in the two classes before the experiment revealed that the students in the two classes were relatively similar in terms of English-speaking level and learning attitude [18]. e main reasons for choosing the second-year students as the subjects of the study are: on the one hand, compared with the third-year students, the second-year students do not have the pressure of the midterm examination and have more class time for teaching oral English every week, which is convenient for the oral teaching study; on the other hand, the second-year students have accumulated a certain amount of vocabulary and English main grammar, which is suitable to be the experimental subjects of oral teaching.…”
Section: Overview Of Computer-assisted Language Teachingmentioning
confidence: 98%
“…WM has been identified as key predictor of L2 learning (Al-Hammadi, 2012;Larsen-Freeman, 2014;Linck et al, 2014) and has been found to impact lexical learning, particularly under instructional conditions (e.g. intentional vocabulary learning) involving simultaneous attention to form and meaning (Ruiz et al, 2021). Therefore, the present study utilised WMTs to assess the learners' ability to retrieve and manipulate auditory information and to detect any variation in the students' recall ability (Climie & Rostad, 2011;Elsayyad, 2014).…”
Section: Study Instrumentsmentioning
confidence: 99%